Using a person-centered approach in clinical care for patients with complex chronic conditions: Perspectives from healthcare professionals caring for Veterans with COPD in the U.S. Veterans Health Administration's Whole Health System of Care. - Ekaterina Anderson; Renda Soylemez Wiener; Brianne Molloy-Paolillo; Megan McCullough; Bo Kim; J Irene Harris; Seppo T Rinne; A Rani Elwy; Barbara G Bokhour (PLoS ONE, 2023)
Background The largest nationally integrated health system in the United States, the Veterans Health Administration (VHA), has been undergoing a transformation toward a Whole Health (WH) System of Care. WH Clinical Care, a component of this system, includes holistically assessing the Veteran's life context, identifying what really matters to the Veteran, collaboratively setting and monitoring personal health and well-being goals, and equipping the Veteran with access to conventional and complementary and integrative health resources. Implementation of WH Clinical Care has been challenging. Understanding healthcare professionals' perspectives on the value of and barriers and facilitators to practicing WH Clinical Care holds relevance for not only VHA's efforts but also other health systems, in the U.S. and internationally, that are engaged in person-centered care implementation. Objectives We sought to understand perspectives of healthcare professionals at VHA on providing WH Clinical Care to Veterans with COPD, as a lens to understand the broader issue of WH Clinical Care for Veterans living with complex chronic conditions. Design We interviewed 25 healthcare professionals across disciplines and services at a VA Medical Center in 2020-2021, including primary care providers, pulmonologists, palliative care providers, and chaplains. Interview transcripts were analyzed using qualitative content analysis. Key results Each element of WH Clinical Care raised complex questions and/or concerns, including: (1) the appropriate depth/breadth of inquiry in person-centered assessment; (2) the rationale for elicitation of what really matters; (3) the feasibility and appropriate division of labor in personal health goal setting and planning; and (4) challenges related to referring Veterans to a broad spectrum of supportive services. Conclusions Efforts to promote person-centered care must account for healthcare professionals' existing comfort with its elements, advocate for a team-based approach, and continue to grapple with the conflicting structural conditions and organizational imperatives.